Implementasi Green Economy Dalam Perspektif Islam: Tinjauan Terhadap Kebijakan Pembangunan Dan Berkelanjutan - Suci Mardiyah; Mohd Winario; Zubaidah Assyifa; Yudi Irwan (Journal of Economic, Management, Business, Accounting Sustainability, 2026)
This study aims to comprehensively examine how the implementation of a green economy can be understood and operationalized from an Islamic perspective through a review of sustainable development policies. The method used is a qualitative-descriptive approach with a literature review of academic sources, international and national policy reports, and contemporary Islamic economics literature. The results of the study indicate that green economy principles such as resource efficiency, low-carbon development, social inclusiveness, and ecosystem protection are normatively aligned with the objectives of the maqāṣid al-sharī‘ah (Islamic principles), particularly in safeguarding religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), progeny (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). In the context of sustainable development policies, the implementation of an Islamic-based green economy is reflected in policy instruments that encourage green investment, equitable natural resource management, the strengthening of sustainable Islamic finance, such as green sukuk, and regulations that limit overexploitation and environmental damage. However, this study also identifies several challenges, including the limited integration of Islamic values ​​in public policy formulation, the dominance of conventional economic paradigms focused solely on growth, and weak coordination among stakeholders. Therefore, this article emphasizes the importance of mainstreaming Islamic economic values ​​in sustainable development policies so that the implementation of a green economy is not merely technocratic but also grounded in ethics and moral responsibility, thereby achieving sustainable, equitable prosperity aligned with long-term development goals.